Papel da família no processo de ensino aprendizagem: quando o excesso de superproteção se torna um problema? - Andrade, Andriele Souto de (Universidade Federal do Tocantins, 2023)
This research sought to understand the extent to which parental overprotection can influence a child's development. For this, and in order to analyze the problem in detail and in depth, it was necessary to know John Bowlby and understand how the Attachment Theory emerged, identifying the fundamental aspects and principles of his work, which provides necessary elements to discuss the role and importance of attachment in child development. Thus, the aim of this work was to understand the impact of an overprotective education on children's development, as well as to understand whether parental overprotection can, in fact, influence the development of children's skills and acquisitions.